Syariah Pawnship in Indonesia: Analysis of Fiqh and Its Practice in Syariah Financial Institutions - Mustaniroh, Mustaniroh; Musadad, Ahmad; Zahro, Umi Indasyah; Pujiati, Tri (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
Economic and business developments are always accompanied by developments in capital requirements and additional business capital facilities which always require guarantees to maintain the security of the capital provided. business. Pawning is a type of debt and receivable agreement and has been in place since the time of the Prophet. Over time pawnshop institutions were formed to encourage economic survival. This research aims to explain various aspects of sharia pawning starting from the history, legal basis of sharia pawning to the implementation of pawning in both banking and pawnshop institutions in Indonesia. This research is research with a qualitative descriptive approach using documentation studies through references related to sharia pawning in Indonesia. The research results show that sharia pawn operations in Indonesia do not conflict with Islamic sharia (Al-Qur'an, Hadith, Ijma, and DSN Fatwa). Not only that, the principle of pawning is actually in line with maqashid sharia, namely the protection of property, body, mind, offspring and soul. Handling problems at sharia pawnshops by providing several ways to pay off and not adding to the burden of deposits and administration costs. The results of this research provide recommendations that the implementation of sharia pawning can be implemented in the community for the benefit of the people.